Currículo de matemática da Educação de Jovens e Adultos: uma análise baseada em livros didáticos - Santana, Kátia Cristina Lima (2012)
This research aims at analysing the Mathematics curriculum presented to the Youth and Adult Education, under the perspective of the enculturator curriculum proposed by Bishop (1999). It will be guided by the leading-question: the contents addressed in Mathematics books for Youth and Adult Education, methodologies, organization and contexts lead to the mathematics enculturation processes? In order to answer, the question has been unfolded into: (1) the elements presented in the activities on textbooks provide mathematics enculturation? (2) How is the content organization presented? (3) What options the activities show in relation to the choice of contents? This is a qualitative research, document analysis type, in which two Mathematics textbooks collections were analysed, being approved by the PNLD-EJA. The theoretical foundations of the study are Alan Bishop s ideas concerning Mathematics as a cultural phenomenon and the enculturator curriculum; Célia Pires essays on curricular organization and Ole Skovsmose works with regards to the criteria for the choice of environmental contexts for mathematics learning will also be used. Through the analysis of the textbooks, based on the categories chosen from the theoretical reference, it is concluded that textbooks for the Youth and Adult Education present, in some of its approaches and activities, elements that support mathematics enculturation. Moreover, we came to the conclusion that the Mathematics curriculum, in all its dimensions, including and, especially, when it comes to the curriculum presented and practiced in the classroom, must provide a constructive environment of mathematics acquirements, in which addressed contents are rich in contexts that represent the mathematics culture; accessible to the student; formalize the concepts appropriately to the construction of knowledge; evidence the explanatory power of Mathematics; concepts which are built from meaningful activities and based on the student s reality; use a wide range of methodologies; and, lastly, which are arranged in order to overcome the traditional linear organization